Estimating the cost of calibration services using the TDABC costing method - Arenhart, Rodrigo Schons; Mendes, Angélica Alebrant; Pizzolato, Morgana (Revista Gestão da Produção Operações e Sistemas, 2020)
The activity-based costing method (TDABC) emerged in the 2000s as a simplification of the activity-based costing method (ABC). Its purpose is to facilitate and reduce the costs of costing system implementation. This paper aims to estimate the cost of calibrating scales, micrometers, and calipers of a higher education laboratory through the TDABC costing method, to then evaluate the applicability of the method and to define a minimum number of calibrations to let the laboratory reach its equilibrium point. The implementation of the methodology took the following steps: i) identify activities of each service and duration times; ii) calculate the practical capacity and its costs and; iii) determine the capacity rate and multiply it by the activity times. The identification of the costs of each activity for each service analyzed, the clear verification of the method determining its applicability, the estimation of the minimum number of annual calibrations for the laboratory to reach its break-even point, and the visualization of greater financial attractiveness for the service of calibration of scales form the main results obtained.